Un texte de la religion kaumāra : le Tirumurukārruppaṭai - Nakkīrar (Publications de l'Institut français d'indologie, 1973)
Hymn to Murugan, Hindu deity; the first poem in Pattupāṭṭu, an anthology of the Third Sangam.